AGAINST RELIGIOUS SLAVERY AND OPPRESION IN RIDLEY SCOTT’S KINGDOM OF HEAVEN MOVIE (2005): A MARXIST APPROACH - PRIMAYOGI, DANANG (2011)
This research paper is focused to analyze the movie based on its structural elements and to analyze the class struggle of major character based on Marxist perspective on the religious in the movie kingdom of heaven. The researcher employs qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data sources are taken from attitude, dialogue and all statement in the text of the movie which are relevant with the research. The secondary data sources are the books about the social historical background of Jerusalem society and the other source such as internet that are relevant with the research. The method of data collection is library research based on literary sources and the technique of data collection is descriptive qualitative analysis. Based on the analysis, the result of this study is as follows. Firstly, the structural elements and technical elements in kingdom of heaven movie can support the theme. The director wants to deliver the theme that freedom is not given but must be struggled for. Secondly, this movie contains values that represent Marxist principles, especially on the dialectical materialism, historical materialism, alienation, class struggle, revolution and ideology.